2021
DOI: 10.1029/2021jg006378
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Trait Covariation and Its Controls: A Quantitative Data Analysis Along a Subtropical Elevation Gradient

Abstract: Elevation gradients provide a "natural experimental" setting in which ecological and community processes and responses to changing environments can be tested (Pfennigwerth et al., 2017;Wang et al., 2014). The stark climatic differences along short horizonal gradients in mountain environments make them natural experimental areas for studying how plants respond to sudden environmental changes (Midolo et al., 2019). Plants undergo natural selection and evolve an optimal phenotype for adaptation to a given environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In addition, the study of phenotypic variation along elevation gradients has been useful to examine trait-environment relationship across both species and lineages [ 42 ]. This information is crucial to understand how environmental selection drives phenotypic adjustments in traits that impact on the fitness of individuals, promoting an efficient exploitation of resources in a given environment, and how consistent are those adjustments across lineages [ 43 ]. At the same time, it allows us to understand how the differential use of resources supported by the trait-environment relationship allows species to coexist in an area, impacting the patterns of diversity and differentiation observed along strong environmental gradients, thus defining the composition and structure of communities [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study of phenotypic variation along elevation gradients has been useful to examine trait-environment relationship across both species and lineages [ 42 ]. This information is crucial to understand how environmental selection drives phenotypic adjustments in traits that impact on the fitness of individuals, promoting an efficient exploitation of resources in a given environment, and how consistent are those adjustments across lineages [ 43 ]. At the same time, it allows us to understand how the differential use of resources supported by the trait-environment relationship allows species to coexist in an area, impacting the patterns of diversity and differentiation observed along strong environmental gradients, thus defining the composition and structure of communities [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is evident in attributes such as reduced leaf size, lower specific leaf area, thicker leaf, higher leaf length-to-width ratio, and lower vein density. Contrarily, the abundance of resources at lower elevations can result in a resource-acquisitive strategy, leading to larger leaf size, higher specific leaf area, thicker leaf, and lower vein density (Marod et al 2018;Midolo et al 2019;Ochoa-beltrán et al 2021;Yang et al 2021). Some of the important leaf traits indicative of either resource-use or resource-acquisitive strategy include leaf area, specific leaf area, leaf thickness, leaf toughness, vein density, leaf mass to area ratio (LMA), leaf length to width ratio, leaf nitrogen mass (Nmass), leaf nitrogen area (Narea), and among others (Cruz-Maldonado et al 2021;Midolo et al 2019;Sack and Scoffoni 2013;Shi et al 2018;Yang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, the abundance of resources at lower elevations can result in a resource-acquisitive strategy, leading to larger leaf size, higher specific leaf area, thicker leaf, and lower vein density (Marod et al 2018;Midolo et al 2019;Ochoa-beltrán et al 2021;Yang et al 2021). Some of the important leaf traits indicative of either resource-use or resource-acquisitive strategy include leaf area, specific leaf area, leaf thickness, leaf toughness, vein density, leaf mass to area ratio (LMA), leaf length to width ratio, leaf nitrogen mass (Nmass), leaf nitrogen area (Narea), and among others (Cruz-Maldonado et al 2021;Midolo et al 2019;Sack and Scoffoni 2013;Shi et al 2018;Yang et al 2021). The specific leaf area, leaf life span, massbased nitrogen, and mass-based assimilation are some traits associated with the plant's growth, survival, and light requirement (Poorter and Bongers 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the abiotic environment along elevational gradients also cause variations in functional leaf traits (Read et al, 2014 ). For example, leaf size and specific leaf area (SLA) generally decrease with increasing elevation (Midolo et al, 2019 ; Wright et al, 2017 ), whereas leaf water content tends to increase (Cruz‐Maldonado et al, 2021 ; Yang et al, 2021 ), despite the considerable variations in elevational patterns reported among individual studies. All these traits are associated with plant quality for herbivores (Callis‐Duehl et al, 2017 ; Wright et al, 2004 ), so their changes can contribute to elevational changes in herbivory.…”
Section: Introductionmentioning
confidence: 99%